12a2b + 6a = 6a(2ab + 1)
b/2=2ab/+b means112.5
5ab-2ab+4a-b+5b = 3ab+4a+4b
a square plus 2ab plus b square
12a2/(2ab) = 6a/b
(a+b)(a+b)Also equal to a2+2ab+b2
No. If you expand (a + b)2 you get a2 + 2ab + b2. This is not equal to a2 + b2
Remember to factor out the GCF of the coefficients if there is one. A perfect square binomial will always follow the pattern a squared plus or minus 2ab plus b squared. If it's plus 2ab, that factors to (a + b)(a + b) If it's minus 2ab, that factors to (a - b)(a - b)
the answer to factorising (a x a3 + 2ab + b2) would be (a4+2ab+b2)
12a2b + 6a = 6a(2ab + 1)
(a + b)² = a² + b². If you expand the left side, you have a² + 2ab + b² = a² + b². Subtracting a² and b² from both sides, you have: 2ab = 0. So if either a=0 or b=0 the equation is satisfied.
(a+b)^2=a^2+b^2+2ab it should read "the quanitity "a plus b" squared equals a squared plus b squared plus two a times b" See related link below for a picture that shows it graphically.
b2 + ab - 2 - 2b2 + 2ab = -b2 + ab - 2 which cannot be simplified further.
b/2=2ab/+b means112.5
No, ab squared is not the same as 2ab. ab squared (ab^2) means multiplying ab by itself, resulting in a^2 * b^2. On the other hand, 2ab means multiplying 2 by a and then by b, resulting in 2ab. These two expressions are not equivalent because ab^2 involves squaring the variable b, while 2ab does not involve squaring any variables.
A^2-2ab+B^2 is actually (A+B)^2 AB squared is A^2B^2 or (AB)^2
5ab-2ab+4a-b+5b = 3ab+4a+4b